2021
DOI: 10.1186/s12933-021-01358-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal hemodynamic effects differ between antidiabetic combination strategies: randomized controlled clinical trial comparing empagliflozin/linagliptin with metformin/insulin glargine

Abstract: Background Type 2 diabetes causes cardio-renal complications and is treated with different combination therapies. The renal hemodynamics profile of such combination therapies has not been evaluated in detail. Methods Patients (N = 97) with type 2 diabetes were randomized to receive either empagliflozin and linagliptin (E+L group) or metformin and insulin glargine (M+I group) for 3 months. Renal hemodynamics were assessed with para-aminohippuric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…An initial decline in eGFR is a well‐known phenomenon after starting an SGLT2 inhibitor and the observed effects in the present trial are consistent with previous studies 28,29 . The mechanisms by how SGLT2 inhibitors modulate renal haemodynamics are not completely understood, but studies in patients with type 2 diabetes and preserved kidney function have suggested that dilation of postglomerular arterioles are probably involved in the haemodynamic effects of SGLT2 inhibitors 27,30,31 . Emerging data suggest that SGLT2 inhibitors can both constrict afferent arterioles and dilate efferent arterioles 27,30 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An initial decline in eGFR is a well‐known phenomenon after starting an SGLT2 inhibitor and the observed effects in the present trial are consistent with previous studies 28,29 . The mechanisms by how SGLT2 inhibitors modulate renal haemodynamics are not completely understood, but studies in patients with type 2 diabetes and preserved kidney function have suggested that dilation of postglomerular arterioles are probably involved in the haemodynamic effects of SGLT2 inhibitors 27,30,31 . Emerging data suggest that SGLT2 inhibitors can both constrict afferent arterioles and dilate efferent arterioles 27,30 .…”
Section: Discussionsupporting
confidence: 89%
“…28,29 The mechanisms by how SGLT2 inhibitors modulate renal haemodynamics are not completely understood, but studies in patients with type 2 diabetes and preserved kidney function have suggested that dilation of postglomerular arterioles are probably involved in the haemodynamic effects of SGLT2 inhibitors. 27,30,31 Emerging data suggest that SGLT2 inhibitors can both constrict afferent arterioles and dilate efferent arterioles. 27,30 However, it should be noted that efferent postglomerular arterioles have smaller diameters than preglomerular arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…Large outcome trials in patients with CHF demonstrate that there are no additional safety findings in patients treated with SGLT2 inhibitors and RAS inhibitors. 1 , 2 , 20 Previous studies in patients with T2DM suggest that SGLT2 inhibitors exert part of their beneficial effects via post‐glomerular vasodilation, 21 , 22 , 23 which is also one major nephroprotective action of ACEI/ARBs. Combining these two drug classes therefore possibly has an additive effect regarding renal haemodynamic function.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional treatments to maintain blood glucose levels do not always prevent DKD [ 13 ]. On the other hand, it was reported that sodium–glucose cotransporter-2 (SGLT2) inhibitors, which are quite novel but already a widely used therapy, may prevent the development and alter the natural progression of DKD by inducing systemic and glomerular hemodynamic changes, providing metabolic advantages, and diminishing inflammatory and oxidative stress pathways [ 1 , 14 , 15 , 16 , 17 ], which we have shown in the Figure 1 .…”
Section: Introductionmentioning
confidence: 96%